A phase transition enhances the catalytic activity of SARM1, an NAD+ glycohydrolase involved in neurodegeneration - Heather S Loring; Victoria L Czech; Janneke D Icso; Lauren O'Connor; Sangram S Parelkar; Alexandra B Byrne; Paul R Thompson (eLife, 2021)
Sterile alpha and toll/interleukin receptor (TIR) motif–containing protein 1 (SARM1) is a neuronally expressed NAD+ glycohydrolase whose activity is increased in response to stress. NAD+ depletion triggers axonal degeneration, which is a characteristic feature of neurological diseases. Notably, loss of SARM1 is protective in murine models of peripheral neuropathy and traumatic brain injury. Herein, we report that citrate induces a phase transition that enhances SARM1 activity by ~2000-fold. This phase transition can be disrupted by mutating a residue involved in multimerization, G601P. This mutation also disrupts puncta formation in cells. We further show that citrate induces axonal degeneration in C. elegans that is dependent on the C. elegans orthologue of SARM1 (TIR–1). Notably, citrate induces the formation of larger puncta indicating that TIR–1/SARM1 multimerization is essential for degeneration in vivo. These findings provide critical insights into SARM1 biology with important implications for the discovery of novel SARM1-targeted therapeutics.